2022
DOI: 10.1029/2021jd035710
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Increases of Severe Haze Pollution During the Post COVID‐19 Period: Effects of Emissions, Meteorology, and Secondary Production

Abstract: China has experienced severe haze pollution during the past decade with the rapid development of industrialization and urbanization, which is typically characterized by high concentrations of fine particulate matter (PM 2.5 , aerodynamic diameter less than 2.5 μm) (An et al., 2019;R. Zhang et al., 2015). As a response, a series of stringent measures covering main source sectors have been implemented nationwide in recent years targeting for reducing PM 2.5 , for example, the "Atmospheric Pollution Prevention an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 65 publications
1
7
0
Order By: Relevance
“…The results suggest that the conversion efficiency of secondary aerosols was highest during stage 3 under the most serious pollution, which is consistent with the results of other studies of heavy haze (Huang et al, 2014;Zhou et al, 2022;Shang et al, 2021).…”
Section: Temporal Variation Of the Qda Results In Different Stagessupporting
confidence: 92%
“…The results suggest that the conversion efficiency of secondary aerosols was highest during stage 3 under the most serious pollution, which is consistent with the results of other studies of heavy haze (Huang et al, 2014;Zhou et al, 2022;Shang et al, 2021).…”
Section: Temporal Variation Of the Qda Results In Different Stagessupporting
confidence: 92%
“…The variations of aerosol species can be affected by the changes of both meteorological conditions and emissions. As a result, chemical transport models are often used to estimate the relative impacts of meteorology and emissions from different sources by performing controlled simulations. For example, Zhou et al found that the decreases in OA and sulfate in cold season from 2013 to 2017 were mainly due to the emission reductions, while the changes in nitrate were mainly caused by meteorological variations.…”
Section: Introductionmentioning
confidence: 99%
“…Non-refractory submicron aerosol (NR-PM 1 ) species, including organics (Org), sulfate (SO 4 ), nitrate (NO 3 ), ammonium (NH 4 ) and chloride (Chl) were measured in the V-mode at a time resolution of 1 min. In addition, the NR-PM 2.5 species were measured by a CV-ACSM operated in parallel at a time resolution of 2 min, which was detailed in Zhou et al (2022) . SO 2 , O 3 , CO and NO x concentrations were measured by a suite of gas analyzers (models 43i, 49i, 48i and 42i, respectively, Thermo Scientific).…”
Section: Methodsmentioning
confidence: 99%